The nuncio Alessandro Bavona and the creation of the ecclesiastical province of Cuiabá in 1910 - Marin, Jérri Roberto [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2021)
This article analyzes the policies and strategies of the Holy See to divide the territory of the diocese of Cuiabá and elevate it to the status of archdiocese, having as suffragans the dioceses of Cáceres and Corumbá. The style of mando of bishop Carlos Luiz d'Amour and his ineffective performance, the large territorial extent of the diocese and its low demographic density motivated the interventions of the Holy See. The expansion of ecclesiastical circumscriptions in Mato Grosso aimed to make their governability more efficient, ensuring the control and regulation of individuals and the social body, implement internal reforms, combat competing religions and strengthen the Catholic Church before the State. The sources were obtained from the Vatican Apostolic Archives and the Historical Archive of the Congregation on the Extraordinary Ecclesiastical Affairs, that allow detailing the articulations and projects of the nuncio Alessandro Bavona and secretary of State Raffael Merry Del Val to reform, strengthen and expand the Catholic Church in Brazil.
O núncio Alessandro Bavona e a criação da província eclesiástica de Cuiabá em 1910
Keywords: D. Carlos Luiz d'Amour; Dioceses; Holy See; Mato Grosso; Nunciatura Apostólica